Pediatric imaging : a core review - Blumer, Steven L.; Biko, David M.; Halabi, Safwan (Core review series., 2018)
"Key features of this book: contains 300 image-rich ultrasound questions with answers, explanations, and references; features high-quality images that correspond to each question, plus high-yield tables embedded in the answers for additional review and provides answers and rationales as to why an answer is correct and other choices are incorrect."--Publisher